FAKTOR RESIKO DAN KElADIAN LEPTOSPIROSIS DI KABUPATEN PONOROGO (Studi Kasus Di Wilayah Kecamatan Ngrayun Dan Kecamatan Badegan Tahun 2014) - Rahma Ika Pratiwi; Siti Surasri; Koerniasari . (GEMA LINGKUNGAN KESEHATAN, 2014)
Leptospirosis is a zoonotic disease with rodents (rat), pigs, cows, goats, sheep, horses, dogs, cats,birds, insectivores (hedgehogs, bats, squirrels) acting as the reservoir that have been infected by theagent of the disease leptospiroses leptospira bacteria. leptospiroses outbreak in Ponorogo namely inNgrayun Sub District in 2011 until 2013 marked the highest the number of cases. In 2013 an incident ofleptospiroses involved 20 patients in Ngrayun sub district and 7 people in the district Badegan subdistrictand in 2013 leptospiroses appeared for the first time in Badegan. The purpose of this study was todetermine the risk factors and the occurrence of leptospirosis cases in Ngrayun and Badegan subdistrictsof Ponorogo in 2014.The type of this research is descriptive with case study design to assessand describe the conditionof the cases and the associated risk factors . The research subjects were leptospiroses patients and theirhomes. Research variables in this study were the physical environment, biological environment, socialenvironment, and behavioral factors.Results of the observations and interviews using Guttman scale factors included the state of thephysical environment, poor water storage, poor use of river/weill, and the distance of the waste collection.Biological environment factors included the presenceof rats, the presence of farm animals or pets. Socialenvironmental factors included the level of education and type of occupation, they were also poor.Behavioral factors which included the habit of bathing, washing hands, use of footwear, treatment ofwounds, were all in poor state.The final conclusion is that the state of the risk factors, that include the physical environment.biological/ social and behavioral factors are in poor state. These call for counseling and testing of ROTtoimprove knowledge and insiqhts and to change people's behavior and to review the leptospirosesprevention program